Поцелуй ветра: повесть / Ирина Щеглова - Щеглова Ирина Владимировна (Только для девчонок, 2012)
Экземпляры: ф.21 (20211021) / Инвентарный номер: 61337 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Щ 33 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44